Chemical, Thermal, and Morphological Properties of Sustainable Lignocellulosic Biomaterial - Bachir Bouhamida; Abderrazek Merzoug; Zouaoui Sereir; Ali Kilic; Zeki Candan (Drvna Industrija)
By the present paper, an experimental investigation was proposed to compare the morphological, chemical and mechanical properties of the Petiole Date Palm Wood (PDPW) collected from north and south of Algeria. Both regions have very distinctive climatic conditions – wet conditions in the north (near the Mediterranean Sea) and semi-arid conditions in the south Biskra. To achieve this aim, large quantities of waste from PDPW were collected, cleaned, and cut according to the normalization specific to each type of test. After that, scanning electron micrographs, infrared spectroscopy, dynamic mechanical thermal analysis (DMTA) and thermogravimetric analysis were made, and moisture content (MC) and water absorption (WA) were determined, to compare the effect of the different environmental conditions. From the results obtained, petiole date palm wood typical for the southern region had a high fiber content, attributed to its low porosity and excellent mechanical properties, which resulted in low water absorption. In contrast, the northern petiole wood reveals a higher glass transition temperature (Tg) and significant damping coefficient. At comparable relative density values, the specific properties were found to be comparable to those of balsa, foams and metallic honeycombs.